Hands Over Our Ears: Tensions In the Liminal Spaces Concerning English as a Second Language Education for d/Deaf Newcomers to Canada - Black, Ari (Université d'Ottawa / University of Ottawa, 2019)
This thesis by article investigates the question “What discourses are (re)produced by policy documents and administrators relating to ESL programmes for Deaf newcomers to Canada?” The surrounding monograph begins with a description of the research context and a review of the relevant literature and ends with concluding remarks. The article contains a condensed version of the context and literature review, the methodology, discussion, conclusions, and relevance to the field of education. The research uses discourse analysis to examine federal, provincial, and schoolboard documents, and participant interviews. There were two participants, one Deaf and one hearing, who both administer ESL programmes for Deaf newcomers. The findings suggest that both the policy documents and the participants exist in tensions between the majority Discourse and the Deaf community Discourse. This area of research is pertinent to second language education for Deaf newcomers, a growing population in the wake of mass-migrations.
Keywords: English as a Second Language; ESL; American Sign Language; ASL; Deaf; Education; Ideology; Policy; Physionormativity; Physionemic; Physionetic